MASLAHAH DAN NAS - SUATU WACANA SEMASA - Mohamed Naim, Asmadi (Jurnal Syariah, 2019)
This article seeks to explore the issue of ma~/a~ah and nas. The two major areas to be discussed are the application of ma~la~ah in the ijtihiid and the possible instances where m~/a~ah may take precedence over nas. The article will present the two arguments as regards to ma~/a~ah as seen by Najm al-Dzn ai-Tuft and manhiij ulama in determining the hukm based on the principle of maslahah. The article will also outline the rules to be observed in issuing such a hukm so as to ensure that maslahah would not nullify the hukm as decreed by Allah SWT.